The Effect of Brand Awareness, Customer Experience, and Brand Image on Customer Loyalty with Customer Satisfaction as A Mediation Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the effect of Brand Awareness, Customer Experience, and Brand Image on Customer Loyalty with Customer Satisfaction as a mediating variable (a case study of Kawasaki Ninja consumers in Semarang). This research is quantitative in nature. The population consists of Kawasaki Ninja consumers in Semarang City. The sampling technique used was purposive sampling, with a total of 80 respondents. The study employed Partial Least Square (PLS) analysis using SmartPLS version 3. The results show that Brand Image and Customer Experience have a significant effect on Customer Satisfaction, which in turn significantly increases Customer Loyalty. Customer Satisfaction was found to mediate only the effect of Brand Image on Customer Loyalty, while Brand Awareness had no significant effect on either Customer Satisfaction or Customer Loyalty.
Keywords: Brand Awareness; Brand Image; Customer Experience; Customer Satisfaction